Rate of Decay in Proportion of Condom Protected Sex Acts among Adolescents Following Participation in an HIV Risk-Reduction Intervention - DiClemente, Ralph J. (2013)
OBJECTIVE: HIV risk-reduction interventions have demonstrated efficacy in enhancing the proportion of condom protected sex acts (CPS) among diverse populations. While post-intervention exposure increases in CPS are often observed, there is scant empirical data quantifying decay of intervention efficacy (declines in CPS following cessation of the intervention among participants reporting an initial post-intervention increase in CPS). Thus, the objective of this study was to quantify the rate of decay in intervention efficacy over a 24-month follow-up. DESIGN: African-American adolescent females (ages 14–20; N = 349) completed a baseline ACASI, participated in an HIV risk-reduction intervention, and were assessed at 6-month intervals for 24-months post-intervention. Intervention efficacy was conceptualized as an increase in participants’ CPS relative to baseline. METHODS: Analyses focused on the subset of participants who reported an initial increase in CPS from baseline to the 6-month post-intervention assessment (n = 121) to quantify the rate of decay in intervention efficacy over a 24-month follow-up period. RESULTS: CPS increased markedly from baseline to 6-month follow-up assessment. However, from 6- to 12-months, a marked decline in CPS was observed. Further CPS declines, though not statistically significant, were observed from 12- to 18-months and 18- to 24-months. Cumulative reductions in CPS over the entire 24-month follow-up resulted in no statistical difference between baseline and 24-month follow-up; indicative of a non-significant intervention effect at 24-month assessment. CONCLUSIONS: Innovative post-intervention optimization strategies are needed to minimize CPS decay over protracted time periods by reinforcing, sustaining, and potentially amplifying initial gains in condom use.